Recent Research Advances on the Hippo‐Yki Pathway of Crustaceans: Current Knowledge and Potential Applications in Crustacean Aquaculture - Linwei Yang; Yushi Gan; Hengwei Deng; Jianguo He; Xiaopeng Xu (Reviews in Aquaculture, 2025)
The Hippo‐YAP/Yki pathway is critical for the regulation of physiological responses in various biological processes from invertebrates to mammals. Crustaceans, in particular shrimp and crabs, are important food sources worldwide. In response to the needs of crustacean aquaculture and disease control, the regulatory mechanisms of crustacean life activities, especially immunity, have been increasingly emphasized. Emerging clues suggest that Hippo‐Yki pathway is important for immunity and regeneration in crustaceans. In this review, the structure, activation pattern, response mechanism to pathogen invasion, and crosstalk with other signaling cascades of the Hippo‐Yki pathway in aquaculture crustaceans are summarized and its similarities and differences with those in mammals and Drosophila are investigated. Based on this, the roles of the Hippo‐Yki pathway in crustacean immune response and limb regeneration are further discussed, and the application potential of strategies pharmacologically or biologically targeting this pathway for crustacean disease control and breeding is theoretically explored.